WOMEN TAKING BEHAVIOR CHANGE EARLY DETECTION OF CERVICAL CANCER WITH PEER GROUP MODEL AND HEALTH EDUCATION - I'ana Aulia Andari; Sulastri - (Universitas Muhammadiyah Semarang, 2014)
Cervical cancer is a type of cancer that affects most women over the age of 18 or women ofchildbearing age . This cancer is the second deadliest cancer in the world after breast cancer (IARC , 2010) . Location of the anatomy of the neck of the uterus or cervix are located inside thewoman's body causes difficult to see signs appear physiologically Yag . On the other hand thelack of knowledge of a woman neighbor and how to prevent cervical cancer and early detectionis also one of the factors that affect a woman who had cervical cancer entered into the phase ofadvanced stage to lead to death . In this study the authors will take one location within acommunity member in it all of a woman aged 30-60 years as many as 100 people at thegathering twigs which are located in the district Aisyiyah Kartasura, Village Pucangan, Andtook the respondents 86 people. Researchers will divide the group into two groups with differenttreatment given , namely the control group were 43 persons with health education is giventhrough lectures from researchers and experiment groups given 43 models of peer group with arandom sampling technique . The results of this study showed there are significant healtheducation with behavioral models of the peer group on mother did cervical cancer earlydetection between the experimental group with the control group . The behavior of a motherwith stats early detection of cervical cancer both in the experimental group on the post-testeither Behaviour there were 27 ( 62.8 % ) , the behavior is quite 5 people ( 11.6 % ) and poor asmany as 11 people ( 25.6 % ). Whereas the behavior of the control group at post-test behavioralchanges of 34 ( 79.1 % ) respondents were less supportive reduced to 5 respondents ( 11.6 % )who behave fairly , but found the existence of respondents who support either as many as 4people ( 9 , 3 % ) .Keywords : Early detection, Health education, Peer group models, Knowledge, Behavior.